Structural damper for auto-damping mechanical components. (April 2020) - Sakai, Yasunori; Tanaka, Tomohisa
Abstract: This paper describes a direct passive vibration control approach for mechanical components. The passive damper with anisotropic composite structure (P-DACS) is a composite of metal and polymer, and it can be directly integrated into mechanical components. P-DACS can control static and dynamic characteristics with correctly tuned design parameters and material characteristics. Moreover, the damping can be increased without decreasing static stiffness when optimal design parameters and material are selected. Thus, P-DACS can add auto-damping of static and dynamic vibrations to a structural component. Furthermore, the damping ability can be increased simultaneously for multiple elastic vibration modes. Simulations clarifying the characteristics of P-DACS were conducted to indicate the feasibility of integrating P-DACS into structural components.